The Role of Microtubules in Pancreatic Cancer: Therapeutic Progress - Albahde, Mugahed Abdullah Hasan; Abdrakhimov, Bulat; Li, Guo-Qi; Zhou, Xiaohu; Zhou, Dongkai; Xu, Hao; Qian, Huixiao; Wang, Weilin (Frontiers in Oncology, 2021)
Pancreatic cancer has extremely low prognosis, which is a direct result of its high aggressiveness and invasiveness as well as late diagnosis and lack of effective therapies. One of the most crucial drugs with highly optimistic clinical potential to join the fight against cancer are considered to be microtubule-targeting agents. Almost each type acts differently on cancer cells, but with one common and significant result, which is inhibition of cancer cells. We review here functions of microtubule cytoskeletal proteins in tumor cells and comprehensively examine effects of microtubule-targeting agents on pancreatic carcinoma.